Identification of promising genotypes through systematic evaluation for arsenic tolerance and exclusion in rice (Oryza sativa L.) - Murugaiyan, Varunseelan; Ali, Jauhar; Frei, Michael; Zeibig, Frederike; Pandey, Ambika; Wairich, Andriele; Wu, Lin-Bo; Murugaiyan, Jayaseelan; Li, Zhikang (Frontiers Media, 2021)
Rice remains a major staple food source for the rapidly growing world population. However, regular occurrences of carcinogenic arsenic (As) minerals in waterlogged paddy topsoil pose a great threat to rice production and consumers across the globe. Although As contamination in rice has been well recognized over the past two decades, no suitable rice germplasm had been identified to exploit in adaptive breeding programs. Therefore, this current study identified suitable rice germplasm for As tolerance and exclusion based on a variety of traits and investigated the interlinkages of favorable traits during different growth stages. Fifty-three different genotypes were systematically evaluated for As tolerance and accumulation. A germination screening assay was carried out to identify the ability of individual germplasm to germinate under varying As stress. Seedling-stage screening was conducted in hydroponics under varying As stress to identify tolerant and excluder genotypes, and a field experiment was carried out to identify genotypes accumulating less As in grain. Irrespective of the rice genotypes, plant health declined significantly with increasing As in the treatment. However, genotype-dependent variation in germination, tolerance, and As accumulation was observed among the genotypes. Some genotypes (WTR1-BRRI dhan69, NPT-IR68552-55-3-2, OM997, and GSR IR1-5-Y4-S1-Y1) showed high tolerance by excluding As in the shoot system. Arsenic content in grain ranged from 0.12 mg kg−1in Huang-Hua-Zhan (indica) from China to 0.48 mg kg−1in IRAT 109 (japonica) from Brazil. This current study provides novel insights into the performance of rice genotypes under varying As stress during different growth stages for further use in ongoing breeding programs for the development of As-excluding rice varieties for As-polluted environments.